Influence of technological dose of irradiation on mechanical and electrical characteristics of polymeric insulation of wires - Bezprozvannych, G.V.; Mirchuk, I.A. (Вопросы атомной науки и техники, 2018)
Creation of cables and wires with polymer insulation without halogens based on ethylene vinyl acetate with a high content of fire retardants is impossible without radiation modification properties. On the industrial accelerator of charged particles, the effect of ionizing radiation on wires with a copper conductor cross section of 1.0 mm² and an insulation thickness of 0.7 mm is performed. The influence of the electron energy at identical irradiation factors on the increase in the mechanical strength of insulation during stretching is shown. For electron energy of 0.5 MeV, an increase in the mechanical strength of insulation at a tension of 27% was established, the insulation resistance more than doubled, and the breakdown voltage by 35% at the optimum radiation dose relative to the unirradiated state.